KAJIAN PERTUMBUHAN DAN HASIL TIGA VARIETAS BAWANG MERAH PADA BERBAGAI KEPADATAN POPULASI YANG DITANAM DI LAHAN KERING MARGINAL KECAMATAN SUNGAI RAYA KABUPATEN HULU SUNGAI SELATAN - Abdul Rahman; Jamzuri Hadie; Chatimatun Nisa (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The study on the growth and yield of three onion varieties in various population density planted in the marginal dryland in the District of Sungai Raya, the Regency of Hulu Sungai Selatan was conducted from December 2014 until March 2015, aiming at analysis the effect of the interaction of three onion varieties with three population density towards the growth and yield. This research used Split Plot Design arranged in random groups consisting of 2 treatment factors and 3 replications. The observation data were analyzed and continued with a further test using Duncan’s Multiple Range Test (DMRT) at 5% significant level. The mainplot treatment used three onion varieties and a subplot with 3 spacing of 20 cm x 15 cm, 20 cm x 20 cm, and 20 cm x 25 cm. The research result shows that (1) there is not any interaction between varieties and spacing towards the plant height, number of bulbs, diameter of bulbs, fresh weight of bulbs, dry weight of bulbs, and growth rate (GR) of plants, and (2) there is an interaction between the application of Batu Ijo variety and plant spacing of 20 cm x 20 cm able to increase of onion production per hectare and production per plot.